Interactions between biochar and mycorrhizal fungi in a water-stressed agricultural soil - Mickan, B.; Abbott, L.; Stefanova, Katia; Solaiman, Z. (2016)
© 2016, Springer-Verlag Berlin Heidelberg. Biochar may alleviate plant water stress in association with arbuscular mycorrhizal (AM) fungi but research has not been conclusive. Therefore, a glasshouse experiment was conducted to understand how interactions between AM fungi and plants respond to biochar application under water-stressed conditions. A twin chamber pot system was used to determine whether a woody biochar increased root colonisation by a natural AM fungal population in a pasture soil (‘field’ chamber) and whether this was associated with increased growth of extraradical AM fungal hyphae detected by plants growing in an adjacent (‘bait’) chamber containing irradiated soil. The two chambers were separated by a mesh that excluded roots. Subterranean clover was grown with and without water stress and harvested after 35, 49 and 63 days from each chamber. When biochar was applied to the field chamber under water-stressed conditions, shoot mass increased in parallel with mycorrhizal colonisation, extraradical hyphal length and shoot phosphorus concentration. AM fungal colonisation of roots in the bait chamber indicated an increase in extraradical mycorrhizal hyphae in the field chamber. Biochar had little effect on AM fungi or plant growth under well-watered conditions. The biochar-induced increase in mycorrhizal colonisation was associated with increased growth of extraradical AM fungal hyphae in the pasture soil under water-stressed conditions.